Molecular and neurodevelopmental benefits to children of closure of a coal burning power plant in China. - Deliang Tang; Joan Lee; Loren Muirhead; Ting Yu Li; Lirong Qu; Jie Yu; Frederica Perera (PLoS ONE, 2014)
Polycyclic aromatic hydrocarbons (PAH) are major toxic air pollutants released during incomplete combustion of coal. PAH emissions are especially problematic in China because of their reliance on coal-powered energy. The prenatal period is a window of susceptibility to neurotoxicants. To determine the health benefits of reducing air pollution related to coal-burning, we compared molecular biomarkers of exposure and preclinical effects in umbilical cord blood to neurodevelopmental outcomes from two successive birth cohorts enrolled before and after a highly polluting, coal-fired power plant in Tongliang County, China had ceased operation. Women and their newborns in the two successive cohorts were enrolled at the time of delivery. We measured PAH-DNA adducts, a biomarker of PAH-exposure and DNA damage, and brain-derived neurotrophic factor (BDNF), a protein involved in neuronal growth, in umbilical cord blood. At age two, children were tested using the Gesell Developmental Schedules (GDS). The two cohorts were compared with respect to levels of both biomarkers in cord blood as well as developmental quotient (DQ) scores across 5 domains. Lower levels of PAH-DNA adducts, higher concentrations of the mature BDNF protein (mBDNF) and higher DQ scores were seen in the 2005 cohort enrolled after closure of the power plant. In the two cohorts combined, PAH-DNA adducts were inversely associated with mBDNF as well as scores for motor (p = 0.05), adaptive (p = 0.022), and average (p = 0.014) DQ. BDNF levels were positively associated with motor (p = 0.018), social (p = 0.001), and average (p = 0.017) DQ scores. The findings indicate that the closure of a coal-burning plant resulted in the reduction of PAH-DNA adducts in newborns and increased mBDNF levels that in turn, were positively associated with neurocognitive development. They provide further evidence of the direct benefits to children's health as a result of the coal plant shut down, supporting clean energy and environmental policies in China and elsewhere.